1998
DOI: 10.2307/3579964
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Lymphoma Induction by Long-Term Exposure of Eμ-Pim1 Transgenic Mice to 50 Hz Magnetic Fields

Abstract: E mu-Pim1 transgenic mice expressing a dysregulated Pim1 oncogene in their lymphoid cells were used to test whether exposure to 50 Hz magnetic fields can increase the frequency of malignant lymphoma in mice of a strain predisposed to develop such tumors spontaneously at low incidence. Specific-pathogen-free female mice were allocated randomly into groups of approximately 100 at 6-8 weeks of age and then exposed for 20 h/day for up to 18 months to sinusoidal magnetic fields of 0, 1, 100 or 1000 microT, or 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…The lymphoma incidence and survival rate were indistinguishable. Our data are consistent with the findings of Harris et al (34), who exposed E-Pim1 transgenic mice, which express a dysregulated Pim1 oncogene in their lymphoid cells, for up to 18 months to sinusoidal (1-1000 T) or pulsed (1000 T) 50 Hz magnetic fields and did not observe differences in spontaneous lymphoma development.…”
Section: Discussionsupporting
confidence: 95%
“…The lymphoma incidence and survival rate were indistinguishable. Our data are consistent with the findings of Harris et al (34), who exposed E-Pim1 transgenic mice, which express a dysregulated Pim1 oncogene in their lymphoid cells, for up to 18 months to sinusoidal (1-1000 T) or pulsed (1000 T) 50 Hz magnetic fields and did not observe differences in spontaneous lymphoma development.…”
Section: Discussionsupporting
confidence: 95%
“…Several studies reported that the ELF-EMF has no effect on cognitive behaviors such as attention, performance and memory span (Cook et al, 2006;Kurokawa et al, 2003;Trimmel and Schweiger, 1998). Another study also reported that long-term radiation exposure to 50 Hz and 500 μT has significant effect on the mobility of irradiated animals (Harris et al, 1998). Taken together, these results confirm that the ELF-EMF is able to induce behavioral changes under certain conditions (Ossenkopp et al, 1986).…”
Section: Discussionsupporting
confidence: 65%
“…After 10 months of age, nonlymphoblastic lymphomas predominate (83,112). These mice are susceptible to point-mutation-inducing genotoxic carcinogens such as ENU (113,114) and to other genotoxic carcinogens including X-irradiation (90), benzo[a]pyrene (115), and the heterocyclic amine 2-amino-1-methyl-6-phenylimidazo- [4,5-b]pyridine (116).…”
Section: Resultsmentioning
confidence: 99%
“…In the transgenic models involving the pim oncogene that have been used to test for possible effects of EMF (77,83), pim-1 is linked to the immunoglobulin heavy chain enhancer (Eg). This linkage mimics the chromosomal translocation associated with lymphoid tumors and promotes transgene expression in both T and B cells (105,111).…”
Section: Resultsmentioning
confidence: 99%